Volcanic risk ranking and regional mapping of the Central Volcanic Zone of the Andes - Reyes Hardy, María Paz (2024)
The Central Volcanic Zone of the Andes (CVZA) extends from southern Peru, through the Altiplano of Bolivia, to the Puna of northern Chile and Argentina, between latitudes 14–28° S of the Andean cordillera, with altitudes rising up to more than 4000 m above sea level. Given thelarge number of active volcanoes in this area, which are often located close to both urban areas and critical infrastructure, prioritization of volcanic risk reduction strategies is crucial. The identification of hazardous active volcanoes is challenging due to the limited accessibility, the scarce historical record, and the difficulty in identifying relative or absolute ages due to the extreme arid climate. Here, we identify the highest-risk volcanoes combining complementary strategies:(i) a regional mapping based on volcanic hazard parameters and surrounding density of elements at risk and (ii) the application of the recently developed volcanic risk ranking (VRR) methodology that integrates hazard, exposure, and vulnerability as factors that increase risk and resilience as a factor that reduces risk. We identified 59 active and potentially active volcanoes that not only include the volcanic centres with the most intense and frequent volcanic eruptions (e.g. the El Misti and Ubinas volcanoes, Peru) but also the highest density of exposed elements (e.g. the cities of Arequipa and Moquegua, Peru). VRR was carried out for 19 out of the 59 volcanoes, active within the last 1000 years or with unrest signs, highlighting those with the highest potential impact (i.e. Cerro Blanco in Argentina and Yucamane, Huaynaputina, Tutupaca, and Ticsani in Peru) and requiring risk mitigation actions to improve the capacity to face or overcome a disaster (e.g. volcanic hazard and risk/impact assessments, monitoring systems, educational activities, and implementation of early warning systems).